2013
DOI: 10.1021/ac400896j
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Microfluidic Single-Cell Digital Polymerase Chain Reaction

Abstract: Here we present an integrated microfluidic device for the high-throughput digital polymerase chain reaction (dPCR) analysis of single cells. This device allows for the parallel processing of single cells and executes all steps of analysis, including cell capture, washing, lysis, reverse transcription, and dPCR analysis. The cDNA from each single cell is distributed into a dedicated dPCR array consisting of 1020 chambers, each having a volume of 25 pL, using surface-tension-based sample partitioning. The high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 44 publications
4
84
0
Order By: Relevance
“…Researchers have used microfluidics to integrate cell loading, sample preparation and fluorescent reporter readout for the measurement of several nucleic acid targets in each of 300 cells in an ~2 hour measurement period 50 . Precision fluid routing has been used to aliquot a 60 nl cDNA sample into discrete 25 pl reaction chambers defined by surface tension for digital PCR; carrying out cDNA dilutions in these digital PCR reaction chambers yielded a dynamic range of 0 to 10,000 molecules 51 .…”
Section: Single-cell Measurementsmentioning
confidence: 99%
“…Researchers have used microfluidics to integrate cell loading, sample preparation and fluorescent reporter readout for the measurement of several nucleic acid targets in each of 300 cells in an ~2 hour measurement period 50 . Precision fluid routing has been used to aliquot a 60 nl cDNA sample into discrete 25 pl reaction chambers defined by surface tension for digital PCR; carrying out cDNA dilutions in these digital PCR reaction chambers yielded a dynamic range of 0 to 10,000 molecules 51 .…”
Section: Single-cell Measurementsmentioning
confidence: 99%
“…Furthermore, microfluidic systems offer several key advantages toward the study of single cells including facile automation, parallelization, and reagent reduction. 8 Early researchers found that sample preparation such as cell manipulation, compartmentalization, and lysis was significantly more difficult to implement at the single cell scale compared to in bulk. However, sample preparation preceding molecular analysis has also been miniaturized, allowing facile sample processing.…”
Section: Introductionmentioning
confidence: 99%
“…24 An integrated device was developed to accomplish the necessary steps for single-cell analysis including cell capture, cell lysis, reverse transcription, and digital PCR. 25 However, these devices still need microvalves which are complicated in manufacture and control.…”
Section: Introductionmentioning
confidence: 99%